Adaptive Capacity of Local Governments to Socio-Ecological Challenges: A Case Study in Disaster-Prone Areas in Central Sulawesi - Hans Nayoan; Marlyn Silaen (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study examines the adaptive capacity of local governments in disaster-prone areas of Central Sulawesi, focusing on mechanisms, strategies, and constraints that shape institutional resilience through leadership, coordination, knowledge systems, and community participation. Subjects and Methods: A qualitative case study was conducted in Palu, Sigi, and Donggala using semi-structured interviews, focus group discussions, and document analysis. Participants included government officials, community leaders, and NGO representatives. Thematic analysis was applied to identify patterns related to adaptive governance, learning processes, and collaborative practices. Results: Adaptive capacity is shaped by effective coordination, strong leadership, and robust knowledge systems that support informed decision-making. Community engagement and collaboration with civil society enhance the relevance of adaptive strategies. However, fragmented coordination, weak institutional memory, inconsistent training, and unequal participation of marginalized groups limit the sustainability of adaptive governance and long-term resilience. Conclusions: Strengthening local government adaptive capacity requires integrated, knowledge-based, and inclusive approaches that connect institutional, technical, and community dimensions. Institutionalizing learning, sustaining collaboration, and ensuring equitable participation can shift local governance from reactive disaster management to proactive resilience, offering important insights for policymakers and practitioners.